Isolation and Characterization of Flavonoid Derivative of Ethyl Acetate Extract from Bauhinia latisiliqua Stem Bark and Its Activity as Antioxidant - Sabarwati, Sitti Hadijah; Indriani, Indriani; Nurhaeni, Nurhaeni; Ridhay, Ahmad; Satrimafitrah, Pasjan; Hardi, Jaya; Sikanna, Rismawaty (al Kimiya: Jurnal Ilmu Kimia dan Terapan, 2023)
Various bioactivities on natural compounds, the antioxidant potency can provide a broad spectrum in their utilization and development into medicinal raw material. One of the plants that have potency for antioxidant activity is the Kemerakan sapenit (Bauhinia latisilqua) plant. The study aimed to isolate, characterize, and determine the antioxidant activity of a compound isolated in the ethyl acetate extract of the stem bark of B. latisilqua. This research includes extraction, fractionation, purification, and elucidation of secondary metabolite structure as well as testing its antioxidant activity. Extraction was carried out by maceration technique, fractionation, and purification using liquid vacuum chromatography and gravitation column chromatography. The elucidation of the structural compound was determined by analysis of the UV, IR, and NMR spectra. The antioxidant test was performed using the DPPH method. Based on the analysis of the spectral data, the isolated compound was catechin, a derivative of flavan-3-ol. Antioxidant test on catechin compound showed a strong antioxidant with an IC50 value of 35.01 Âµg /mL (IC50 for positive control, ascorbic acid, of 42.94 Âµg /mL).